Robert Rowland: A Testimony - Bethencourt, Francisco (2023)
Robert Rowland (São Paulo, 1945 - Lisbon, 2023). I will make a short roundup of his partially-known universitary career, followed by the circunstances in which I contacted and worked with him. Rowland's impact in Portuguese scholarship and the influence of his ideas and methods will be examined through this text. It is a personal testimony, obviosuly marked by subjectivity.